Jorunnamycin A Suppresses Stem-Like Phenotypes and Sensitizes Cisplatin-Induced Apoptosis in Cancer Stem-Like Cell-Enriched Spheroids of Human Lung Cancer Cells - Sumkhemthong, Somruethai (Mar Drugs, 2021)
It has been recognized that cancer stem-like cells (CSCs) in tumor tissue crucially contribute to therapeutic failure, resulting in a high mortality rate in lung cancer patients. Due to their stem-like features of self-renewal and tumor formation, CSCs can lead to drug resistance and tumor recurrence. Herein, the suppressive effect of jorunnamycin A, a bistetrahydroisoquinolinequinone isolated from Thai blue sponge Xestospongia sp., on cancer spheroid initiation and self-renewal in the CSCs of human lung cancer cells is revealed. The depletion of stemness transcription factors, including Nanog, Oct-4, and Sox2 in the lung CSC-enriched population treated with jorunnamycin A (0.5 μM), resulted from the activation of GSK-3β and the consequent downregulation of β-catenin. Interestingly, pretreatment with jorunnamycin A at 0.5 μM for 24 h considerably sensitized lung CSCs to cisplatin-induced apoptosis, as evidenced by upregulated p53 and decreased Bcl-2 in jorunnamycin A-pretreated CSC-enriched spheroids. Moreover, the combination treatment of jorunnamycin A (0.5 μM) and cisplatin (25 μM) also diminished CD133-overexpresssing cells presented in CSC-enriched spheroids. Thus, evidence on the regulatory functions of jorunnamycin A may facilitate the development of this marine-derived compound as a novel chemotherapy agent that targets CSCs in lung cancer treatment.